2020
DOI: 10.1186/s12974-020-01864-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal aldosterone elicits a distinct genomic response in pain signaling molecules contributing to inflammatory pain

Abstract: Background: Recently, mineralocorticoid receptors (MR) were identified in peripheral nociceptive neurons, and their acute antagonism was responsible for immediate and short-lasting (non-genomic) antinociceptive effects. The same neurons were shown to produce the endogenous ligand aldosterone by the enzyme aldosterone synthase. Methods: Here, we investigate whether endogenous aldosterone contributes to inflammation-induced hyperalgesia via the distinct genomic regulation of specific pain signaling molecules in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, in CP/CPPS patients, higher NIH-CPSI total and pain domain scores (indicating worse symptom severity) were associated with greater aldosterone levels [ 64 ]. Prior mouse studies demonstrated that aldosterone production leads to hypersensitivity and likely contributes to pain signaling [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in CP/CPPS patients, higher NIH-CPSI total and pain domain scores (indicating worse symptom severity) were associated with greater aldosterone levels [ 64 ]. Prior mouse studies demonstrated that aldosterone production leads to hypersensitivity and likely contributes to pain signaling [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Western blot bands specific for CRF-R1 (56 kDa) or CRF-R2 (38 kDa) according to their data sheet were quantified by Java Image processing and analysis software (ImageJ, open-source image software downloaded from the web#) [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Western blot bands speci c for CRF-R1 (56 kDa) or CRF-R2 (38 kDa) according to their data sheet were quanti ed by Java Image processing and analysis software (ImageJ, open-source image software downloaded from the web# [28,29].…”
Section: Western Blotmentioning
confidence: 99%